2021
DOI: 10.3389/fnins.2021.642176
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Out of Tenascin-C Ameliorates Ischemia-Induced Rod-Photoreceptor Degeneration and Retinal Dysfunction

Abstract: Retinal ischemia is a common pathomechanism in various eye diseases. Recently, evidence accumulated suggesting that the extracellular matrix (ECM) glycoprotein tenascin-C (Tnc) plays a key role in ischemic degeneration. However, the possible functional role of Tnc in retinal ischemia is not yet known. The aim of our study was to explore retinal function and rod-bipolar/photoreceptor cell degeneration in wild type (WT) and Tnc knock-out (KO) mice after ischemia/reperfusion (I/R) injury. Therefore, I/R was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…In contrast, we showed that hypoxic stress has a dramatic effect on the RGCs' electrical activity and their survival rate (Ingensiep et al, 2021). Hypoxia can be induced in vivo by impaired blood flow under high IOP (Andreeva et al, 2014;Wiemann et al, 2021). The findings of our work help to better evaluate and understand the role of pressure stress in glaucoma next to other stressors, such as hypoxia.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, we showed that hypoxic stress has a dramatic effect on the RGCs' electrical activity and their survival rate (Ingensiep et al, 2021). Hypoxia can be induced in vivo by impaired blood flow under high IOP (Andreeva et al, 2014;Wiemann et al, 2021). The findings of our work help to better evaluate and understand the role of pressure stress in glaucoma next to other stressors, such as hypoxia.…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, several studies revealed subtle developmental modifications in the radial glia and oligodendrocyte compartments that were compensated for in the adult CNS [ 74 , 75 ]. Furthermore, recent studies suggested functional roles of Tnc in response to lesions, in particular in the CNS [ 76 , 77 , 78 , 79 ], reviewed in [ 80 ]. Therefore, we decided to investigate the roles of Tnc and Tnr in a myelin lesion model based on the application of cuprizone to the chow [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an enhanced immunostaining of the ECM proteins Tenascin-C and phosphacan/RPTPβ/ζ was identified in S100B optic nerves after 7 days [ 41 ]. Tenascin-C showed enhanced immunoreactivity in the optic nerve after ischemia-reperfusion injury [ 102 ], while a knockout of Tenascin-C could protect the retinal function and rod-photoreceptor cells from ischemic damage [ 103 ].…”
Section: Discussionmentioning
confidence: 99%